Pseudonymization Algorithms for Medical Research: Adoption and Trends...20th World Congress on Medical and Health Informatics (MEDINFO), August 9-13, 2025, Taipei, Taiwan - ABU ATTIEH, Hammam; MÜLLER, Armin; PRASSER, Fabian (Studies in Health Technology & Informatics, 2025)
Pseudonymization is essential for protecting patient privacy in medical research. This paper analyzes pseudonymization algorithms used by common tools employed in medical research in terms of their usage and their development over time. To this, we analyzed documentation, publications, and other available sources, collecting information on algorithms and development timelines. Our findings indicate an evolution from basic encryption and hashing methods to combined and configurable approaches. Recent trends show that flexible solutions that integrate multiple algorithms are becoming increasingly more available.